Evolution of the Insertion-Deletion Mutation Rate Across the Tree of Life. Issue 8 (1st August 2016) - Sung, Way; Ackerman, Matthew S; Dillon, Marcus M; Platt, Thomas G; Fuqua, Clay; Cooper, Vaughn S; Lynch, Michael
Abstract: Mutations are the ultimate source of variation used for evolutionary adaptation, while also being predominantly deleterious and a source of genetic disorders. Understanding the rate of insertion-deletion mutations (indels) is essential to understanding evolutionary processes, especially in coding regions, where such mutations can disrupt production of essential proteins. Using direct estimates of indel rates from 14 phylogenetically diverse eukaryotic and bacterial species, along with measures of standing variation in such species, we obtain results that imply an inverse relationship of mutation rate and effective population size. These results, which corroborate earlier observations on the base-substitution mutation rate, appear most compatible with the hypothesis that natural selection reduces mutation rates per effective genome to the point at which the power of random genetic drift (approximated by the inverse of effective population size) becomes overwhelming. Given the substantial differences in DNA metabolism pathways that give rise to these two types of mutations, this consistency of results raises the possibility that refinement of other molecular and cellular traits may be inversely related to species-specific levels of random genetic drift.